Virtual being: Reflections and Theoretical Perspectives to Understand e-Teaching in Virtuality - Villa-Lombana, Vanessa Del Carmen (2025)
Introduction. This article presents a structured reflection based on the review of theories and concepts that enable an approach to the particularities and complexities of virtual education, and specifically to the meaning of teaching in cyberspace (e-teaching). Purpose. The problematizations raised here aim to stimulate reflection on the training of teachers involved in virtual education. Discussion. This analysis draws on perspectives that offer ways of understanding how we inhabit virtuality, developed mainly by authors such as Paula Sibilia, Pierre Lévy, and Derrick De Kerckhove. Highlighted aspects of Richard Sennett’s work are articulated with his concept of the craftsman, with the aim of outlining a proposal within the scope of educational studies. Conclusions. In light of these issues, training designed for e-teaching broadly and continuously takes on the challenge of imagining and configuring strategies to arrange, provoke, and intertwine the knowledge, experiences, and practices of individuals who navigate cyberspace.